Late Permian and Early Triassic magmatic pulses in the Angara-Taseeva syncline, Southern Siberian Traps and their possible influence on the environment - Paton, M.; Ivanov, A.; Fiorentini, M.; McNaughton, Neal; Mudrovska, I.; Reznitskii, L.; Demonterova, E. (ELSEVIER SCIENCE BV, 2010)
Recently it has been suggested that the major influence on the environment from Siberian Traps magmatism was due to the interaction of magma and organic-rich shale and petroleum-bearing evaporites, with the subsequent creation and outburst of toxic gases (Siberian gas venting: SGV model). In part this idea was supported by a U-Pb age of 252.0 +/- 0.4 Ma for one of the dolerite sills in the southeastern Siberian Traps: the age corresponds to the Permo-Triassic boundary and its known mass extinctions of biota. In this study two other dolerite sills were dated using zircons by the U-Pb SHRIMP method at 254.2 +/- 2.3 Ma and 249.6 +/- 1.5 Ma. The former age is in agreement within error with the age previously published for the dolerite sills, whereas the latter age is in agreement with U-Pb ages published for lava and intrusions from the northern Siberian Traps. The new ages corresponds to the Cahngshingian/Wuchiapingian or Permian/Triassic and Spathian/Smithian boundaries, respectively. Review of Ar-40/Ar-39 and U-Pb SHRIMP ages previously published for the southeastern Siberian Traps shows that three other pulses of magmatism probably took place at respectively Anisian/Spathian, Late/Middle Anisian and Landian/Anisian boundaries. Thus it is possible that the SVG model can be applied also to lesser biotic extinctions and recoveries in proximity and aftermath to the main Permo-Triassic extinction. (C) 2010, V.S. Sobolev IGM, Siberian Branch of the RAS. Published by Elsevier B.V. All rights reserved.